An introduction to Judaism - De Lange, N. R. M. (Nicholas Robert Michael), 1944- (Cambridge ; New York, NY : Cambridge University Press, 2000)
A full and lucid account of Judaism and the Jewish people, written for Jews and non-Jews alike - be they students, teachers, or general interested readers. Contains illustrative tables and maps, a full glossary, chronology, bibliography and index. This is a stimulating and comprehensive introduction to a major world culture.
Cover; Half-title; Title; Copyright; Dedication; Contents; Illustrations; Tables; Preface; Chronology; CHAPTER ONE The Jews in the world; CHAPTER TWO The Jewish people and its past; CHAPTER THREE Jewish books; CHAPTER FOUR The Jewish religion; CHAPTER FIVE The family; CHAPTER SIX The community; CHAPTER SEVEN God and the Jewish people; CHAPTER EIGHT Objectives; CHAPTER NINE Judaism and the future; Glossary; Further Reading; Index.
Includes bibliographical references (pages 238-244) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Jews -- Historiography; Judaism; Judaism; Juifs -- Historiographie; Judaïsme.; Judaism; RELIGION -- Judaism -- General; Jews -- Historiography; Judaism; Judentum; Jodendom; Electronic books; Electronic books